Psychobiological Factors Affecting Cortisol Variability in Human-Dog Dyads. - Iris Schöberl; Manuela Wedl; Andrea Beetz; Kurt Kotrschal (PLoS ONE)
Stress responses within dyads are modulated by interactions such as mutual emotional support and conflict. We investigated dyadic psychobiological factors influencing intra-individual cortisol variability in response to different challenging situations by testing 132 owners and their dogs in a laboratory setting. Salivary cortisol was measured and questionnaires were used to assess owner and dog personality as well as owners' social attitudes towards the dog and towards other humans. We calculated the individual coefficient of variance of cortisol (iCV = sd/mean*100) over the different test situations as a parameter representing individual variability of cortisol concentration. We hypothesized that high cortisol variability indicates efficient and adaptive coping and a balanced individual and dyadic social performance. Female owners of male dogs had lower iCV than all other owner gender-dog sex combinations (F = 14.194, p<0.001), whereas owner Agreeableness (NEO-FFI) scaled positively with owner iCV (F = 4.981, p = 0.028). Dogs of owners high in Neuroticism (NEO-FFI) and of owners who were insecure-ambivalently attached to their dogs (FERT), had low iCV (F = 4.290, p = 0.041 and F = 5.948, p = 0.016), as had dogs of owners with human-directed separation anxiety (RSQ) or dogs of owners with a strong desire of independence (RSQ) (F = 7.661, p = 0.007 and F = 9.192, p = 0.003). We suggest that both owner and dog social characteristics influence dyadic cortisol variability, with the human partner being more influential than the dog. Our results support systemic approaches (i.e. considering the social context) in science and in counselling.